Analysis of the Implementation of the Electronic Medical Record (EMR) System at Kasih Ibu Hospital Surakarta - Fajar Nugroho (PT. Inovasi Teknologi Komputer, 2025)
The use of technology in healthcare services is a key part of modern digital transformation. Despite this progress, many healthcare facilities continue to experience challenges when adopting digital systems. Previous research indicates that these difficulties can significantly affect service quality. Kasih Ibu Hospital Surakarta, which has adopted Electronic Medical Records (EMR), also faces obstacles during the implementation process. This study aims to thoroughly evaluate how EMR is applied at the hospital and identify the factors supporting its adoption. Unlike earlier studies that examined only limited aspects, this research offers a broader perspective. Using a qualitative case study method, data was gathered through questionnaires given to selected participants with relevant education and expertise (purposive sampling). The data was analyzed using the Ishikawa Diagram to pinpoint six major problem areas: human resources, materials, assets, methods, policies, and environment. The findings highlight the importance of continuous monitoring and evaluation of these elements to enhance EMR adoption at the hospital. Ultimately, this study hopes to uncover the main barriers to EMR implementation and assist hospital leaders in developing more effective improvement strategies.